Overview of Musculoskeletal Disorders in Undergraduate Students - Stanisela Agatha; Sayu Aryantari Putri Thanaya; Luh Putu Ratna Sundari; Made Hendra Satria Nugraha (Universitas Udayana dan Diaspora Taipei Medical University, 2022)
Background: Musculoskeletal disorders are defined as complaints or disorders that cause discomfort to the musculoskeletal system. During lecture activities, students are mostly in a static posture. Static and repetitive muscle loading when sitting for a long period can cause muscle fatigue due to the accumulation of lactic acid. Besides, it produces discomfort or pain in the musculoskeletal system. The purpose of the research is to describe an overview of musculoskeletal disorders in undergraduate students of the Bachelor and Professional Program of Physical Therapy Faculty of Medicine Udayana University during the lecture. Methods: The method of this research is descriptive-analytic with a cross-sectional, which has been carried out from October to November 2021. This research used a total sampling technique. The participants were undergraduate students of the Bachelor and Professional of Physical Therapy Program, College of Medicine, Universitas Udayana, with a total of 196 participants who met the established criteria. Researchers measured musculoskeletal disorders using a Nordic Body Map (NBM) questionnaire. Analysis of research data using univariate analysis, namely age, gender, body mass index, study period, duration of the study, and musculoskeletal disorders. Results: The results showed that musculoskeletal disorders were mostly complained of by students, namely the waist 61.7%, then the back 59%, followed by complaints in the lower neck 53.6% and upper neck 47.4% while the lowest complaints occurred in the left leg with a percentage of 5.6%. Conclusion: A total of 177 (90.3%) students had musculoskeletal disorders during lectures and 19 (9.7%) did not experience musculoskeletal disorders during lectures, and 94.4% had a low risk of musculoskeletal disorders. The risk of low musculoskeletal disorders can be interpreted as not requiring improvement.